An Analysis of Occupational Safety and Health Implementation in the Dwelling Place Construction Project, Perkamil Manado : Analisis Penerapan Keselamatan dan Kesehatan Kerja Pada Proyek Konstruksi Dwelling Place Perkamil Manado - Adrian Philip Marthinus; Jermias Tjakra; Grace Yoyce Malingkas (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2026)
Occupational Safety and Health (OSH) is an essential aspect of construction projects to prevent accidents and improve work productivity. The high rate of accidents in the construction sector indicates that the implementation of OSH still needs improvement. This study aims to analyze the implementation of OSH at the Dwelling Place Perkamil Manado construction project, focusing on workers’ compliance with work procedures, the use of personal protective equipment (PPE), the condition of work tools, and the effectiveness of supervision and training. The research employed a descriptive quantitative approach through questionnaires distributed to 23 respondents, field observations, and interviews with project supervisors. The results show that the implementation of OSH in this project is classified as fairly good, with 100% compliance with work procedures and equipment conditions, 65.22% use of PPE, and 78.26% participation in OSH training. Based on the SWOT analysis, the main strengths lie in adherence to standard operating procedures (SOP) and well-maintained equipment, while weaknesses include inconsistent PPE use and the lack of regular training. Overall, the implementation of OSH at the Dwelling Place Perkamil Manado project has been running well, but it requires strengthening through continuous training, supervision, and the development of a sustainable safety culture.